The Role of Village-Owned Enterprises (BUMDes) in Community Economic Empowerment in Sampiran Village, Talun District, Cirebon Regency - Sitti Faoziyah (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Villages are the center of the country's economic activities. Thus, empowerment starts from the lower level, namely the village. The government is now starting to prioritize village development by providing sufficient capital to villages to produce community welfare. This has been stated in the law which specifically regulates village development. Villages have excellent potential for the welfare of the country so they must be mobilized so that the entire community can experience this potential. The presence of BUMDes is an enforcement of numerical law. Regulation Number 6 of 2014 concerning Villages aims to increase community income by mobilizing village potential which is formed directly by community initiative. Related to the problems above, the problem to be solved in this research is how the process of community economic empowerment through BUMDes occurs in Sampiran Village, Talun District, Cirebon Regency. The aim of this research is to understand how the process of community economic empowerment through BUMDes in Sampiran Village, Talun District, Cirebon Province has gone through many stages, namely the sensitive stage, capacity/skills development stage, and business stage. Capital building. Stages, production, marketing and marketing support stages.